2011
DOI: 10.1084/jem.20111354
|View full text |Cite
|
Sign up to set email alerts
|

A genomic storm in critically injured humans

Abstract: Critical injury in humans induces a genomic storm with simultaneous changes in expression of innate and adaptive immunity genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

50
894
5
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,070 publications
(989 citation statements)
references
References 39 publications
50
894
5
14
Order By: Relevance
“…amounts of blood received (total transfusion in milliliters; M = 1,900, MQ = 1,050-3,000), and patient clinical outcomes as indicated by survival (96%), multiorgan failure (maximum Marshall score; M = 5, MQ = 3-7), time to recovery (days; M = 7, MQ = 4-15), nosocomial infections (54.5%), and hospital length of stay (days; M = 21, MQ = 12-32) (15,21). Similarly, in the burn patient population, significant variations existed in the extent of burn injuries, for example, in terms of total body surface area of burns (TBSA; M = 53%, MQ = 32-74%), percentages of flame burns (86%) and inhalation injury (52%), and survival (85%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…amounts of blood received (total transfusion in milliliters; M = 1,900, MQ = 1,050-3,000), and patient clinical outcomes as indicated by survival (96%), multiorgan failure (maximum Marshall score; M = 5, MQ = 3-7), time to recovery (days; M = 7, MQ = 4-15), nosocomial infections (54.5%), and hospital length of stay (days; M = 21, MQ = 12-32) (15,21). Similarly, in the burn patient population, significant variations existed in the extent of burn injuries, for example, in terms of total body surface area of burns (TBSA; M = 53%, MQ = 32-74%), percentages of flame burns (86%) and inhalation injury (52%), and survival (85%).…”
Section: Discussionmentioning
confidence: 99%
“…The Inflammation and Host Response to Injury, Large Scale Collaborative Research Program has completed multiple studies on the genomic responses to systemic inflammation in patients and human volunteers as well as murine models (14)(15)(16)(17)(18). These datasets include genome-wide expression analysis on white blood cells obtained from serial blood draws in 167 patients up to 28 d after severe blunt trauma (15), 244 patients up to 1 y after burn injury, and 4 healthy humans for 24 h after administration of low-dose bacterial endotoxin (14) and expression analysis on analogous samples from well-established mouse models of trauma, burns, and endotoxemia (16 treated and 16 controls per model) (16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory response is generally more protracted than the proinflammatory response, leading to a state of immune suppression in patients surviving the initial "cytokine storm." 16,43 Upon reaching the brain, the proinflammatory signals interact with the resident brain immune system (eg, microglia and astrocyte populations), 3,9,27 causing a neuroinflammatory reaction and consequent neuronal dysfunction; this was shown in preclinical surgical models to affect CNS plasticity in brain regions relevant for higher cognitive functions. [1][2][3][4] We used plasma tau and NFL as markers of acute neuronal injury 39,40 on postoperative days 3 to 4 and at 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a better global understanding of the complex immune response following severe injury in humans, we examined genome-wide expression patterns of blood leukocytes following severe injury, and observed what was termed a 'genomic storm', in which greater than 75% of the host leukocyte transciptome was altered following severe injury (13). More importantly, we demonstrated that genomic information collected in the first 12 hours of severe trauma contained information independent of anatomical and physiological prognosticators that was associated with different clinical outcomes (14).…”
Section: Introductionmentioning
confidence: 99%